A Study on Customer Satisfaction of Telekom Malaysia Broadband - Teoh, Kok Ban; Gan, Kia Hui; Rishimelan, Sangar; Kavithanjli, Munusamy; Yong, Hui Yee; Lee, Jie Min; Lim, Yen Ying (AIBPM Publisher, 2022)
This research aims to investigate how price, service quality, and perceived value affect customer satisfaction among consumers of Telekom Malaysia broadband. This quantitative research distributed an online questionnaire to collect data from 271 current or former customers of Telekom Malaysia Broadband. The findings concluded that service quality and perceived value have significant positive relationships with customer satisfaction, whereas price possesses a significant negative relationship with customer satisfaction. The findings contribute to the continuous improvement on customer satisfaction among consumers of Telekom Malaysia broadband and other telecommunication providers by improving price, service quality, and perceived value.